Intravenously delivered multilineage-differentiating stress enduring cells dampen excessive glutamate metabolism and microglial activation in experimental perinatal hypoxic ischemic encephalopathy. Issue 7 (July 2021) - Suzuki, Toshihiko; Sato, Yoshiaki; Kushida, Yoshihiro; Tsuji, Masahiro; Wakao, Shohei; Ueda, Kazuto; Imai, Kenji; Iitani, Yukako; Shimizu, Shinobu; Hida, Hideki; Temma, Takashi; Saito, Shigeyoshi; et al.
Perinatal hypoxic ischemic encephalopathy (HIE) results in serious neurological dysfunction and mortality. Clinical trials of multilineage-differentiating stress enduring cells (Muse cells) have commenced in stroke using intravenous delivery of donor-derived Muse cells. Here, we investigated the therapeutic effects of human Muse cells in an HIE model. Seven-day-old rats underwent ligation of the left carotid artery then were exposed to 8% oxygen for 60 min, and 72 hours later intravenously transplanted with 1 × 10 4 of human-Muse and -non-Muse cells, collected from bone marrow-mesenchymal stem cells as stage-specific embryonic antigen-3 (SSEA-3)+ and −, respectively, or saline (vehicle) without immunosuppression. Human-specific probe revealed Muse cells distributed mainly to the injured brain at 2 and 4 weeks, and expressed neuronal and glial markers until 6 months. In contrast, non-Muse cells lodged in the lung at 2 weeks, but undetectable by 4 weeks. Magnetic resonance spectroscopy and positron emission tomography demonstrated that Muse cells dampened excitotoxic brain glutamatergic metabolites and suppressed microglial activation. Muse cell-treated group exhibited significant improvements in motor and cognitive functions at 4 weeks and 5 months. Intravenously transplanted Muse cells afforded functional benefits in experimental HIE possibly via regulation of glutamate metabolism and reduction of microglial activation.